PENERAPAN SUPERVISI AKADEMIK KEPALA SEKOLAH SEBAGAI UPAYA PENINGKATAN KINERJA GURU DALAM PENYUSUNAN DAN PENGEMBANGAN PENILAIAN HASIL BELAJAR DI SMA NEGERI 4 BENGKULU SELATAN - Ansridianto Ansridianto (PAKAR Pendidikan, 2015)
The aims of this research is to determine the extent of the coaching principals through academic supervision in improving the performance of teachers in preparing and developing a form of assessment of learning outcomes. In this study conducted in three cycles, the results of action taken is proven to improve the performance of teachers to achieve the ideal standard of 63.39% in the first cycle, can be increased to 68.46% in the second cycle, and the cycle III to 75.09% . The results of this study indicate coaching school action through the principal's Academic supervision can improve the performance of teachers in preparing and developing a form of assessment of learning outcomes with 100% completeness.